Bullet Embolism of Pulmonary Artery: A Rare Case - Ozan Akıncı; Özlem Güngör; Sefa Ergün (Van Tıp Dergisi, 2021)
Bullet embolism of pulmonary artery is a vascular traumatic entity that is a very rare but with serious complications. The bullet can lead to vascular embolism by entering directly into the intravascular area or by migration. In pulmonary artery bullet embolism, complications with high mortality such as thrombosis, sepsis, endocarditis, cerebral stroke may be encountered. Observation and follow-up are sufficient in asymptomatic venous bullet embolism cases. In this case report, we aimed to share our experience with a patient who developed a bullet embolism of pulmonary artery as a result of gunshot injury from the right iliac region.